An Experimental Analysis of Ending Rules in Internet Auctions - Dan Ariely; Axel Ockenfels; Alvin E. Roth (Center for Economic Studies and ifo Institute (CESifo), 2003)
A great deal of late bidding has been observed on internet auctions such as eBay, which employ a second price auction with a fixed deadline. Much less late bidding has been observed on internet auctions such as those run by Amazon, which employ similar auction rules, but use an ending rule that automatically extends the auction if necessary after the scheduled close until ten minutes have passed without a bid. This paper reports an experiment that allows us to examine the effect of the different ending rules under controlled conditions, without the other differences between internet auction houses that prevent unambiguous interpretation of the field data. We find that the difference in auction ending rules is sufficient by itself to produce the differences in late bidding observed in the field data. The experimental data also allow us to examine how individuals bid in relation to their private values, and how this behavior is shaped by the different opportunities for learning provided in the auction conditions.
Keywords: 330